Caracterização da pobreza e desigualdade de renda por setor de atividade econômica no Ceará - 2023 - Meneses, Felipe Aguiar de (2025)
The objective of this work is to characterize poverty by sectors of economic activity and income inequality in Ceará, using statistics and indexes. Although it does not cover all dimensions of poverty and makes it possible to quantify and identify individuals in vulnerable situations, it seeks to analyze the poverty situation in Ceará in 2023, taking into account a geographic, gender and sectoral breakdown based on the Continuous National Household Sample Survey (PNAD Continua). Poverty is a broad social phenomenon, which makes a precise definition necessary to understand the phenomenon. In terms of characterization, it can be said that the conceptual basis of the vision of absolute poverty is related to elementary needs, starting with physical needs. The poverty line is an economic indicator that defines a minimum level of income necessary for a person or family to meet their basic needs, such as food, housing, clothing, health and education. An individual who lives on a per capita income of less than US$6.85 per day (R$638 per month) is considered poor, while anyone who lives on less than US$2.15 per day (R$200 per month) is considered destitution. This metric seeks to measure poverty, in the sense of deprivation of resources, in order to compare poverty. For this purpose, the poverty measures proposed by Foster, Greer and Thorbecke (1984) and the Gini Index are used. Similar to poverty indicators, income inequality was calculated for different geographic regions, population groups, and activity sectors, where we observed great income inequality in the state, which reported a Gini index of 0.510, a lower value than that observed for the RMF, which reported a Gini of 0.540, the region with the highest income concentration in the state in 2023. Throughout this work, we verified that the economic sectors with the highest income in Ceará in 2023 were Public Administration, Education, and IT, respectively. On the other hand, Domestic Services has the lowest income level, followed by the agriculture sector. Among the income levels, income from Labor was significantly higher than the other two income levels, with emphasis on Public Administration, Education, and IT.